Breaching bodily boundaries: posthuman (dis)embodiment and ecstatic speech in lip-synch performances by boychild. Issue 2 (3rd July 2017) - Riszko, Leila
ABSTRACT: Employing a sci-fi inspired aesthetic, queer, black, trans artist, boychild presents audiences with a future vision of human embodiment. Strobe lighting makes her appear fragmented or as if she were a hologram. An electronic light flickers behind her teeth. Her eyes are obscured by whited-out contact lenses. boychild's is a body interfaced with technology. She is imaged as non-human, cyborgian. Whilst boychild considers her onstage persona to be female, her body reads ambiguously. Transgressing demarcations between the supposedly polarised categories of organic/machine, male/female, the queer form of embodiment she presents is posthuman. Implementing the theoretical principles of Rosi Braidotti's anti-humanist concept of the posthuman and Donna Haraway's cyborg politics, I argue that boychild's engagement with the posthuman does not end with aesthetics, rather it extends to the plotting of a posthuman politics, posing a radical challenge to heteronormative body politics. Theorising boychild's lip-synch performances, I argue for her style of performance as a technologised form of ventriloquism, as she 'speaks' with the voice of another or the voice of another speaks through her. Using Mladen Dolar's and Slavoj Žižek's psychoanalytical philosophies in conjunction with Steven Connor's literature on ventriloquism, I unpick the intricacies of presence and power inherent to her 'voice' and indicate its broader political implications.